Penerapan Automatic Disinfection Chamber Untuk Pencegahan Covid19 di Pondok Pesantren Al Mujaddadiyah - Triyono, Budi; Prasetyo, Yuli; Ningrum, Hanifah Nur Kumala; Haryo, Raden Jasa Kusumo; Winarno, Basuki; R., Aldanur I. (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2020)
Indonesia is currently included in the covid19 virus pandemic category. Many cities have been hit by the Covid19 virus. The city of Madiun has also been confirmed positive for the Covid19 virus. Therefore, to prevent the transmission of the Covid19 virus, prevention efforts are needed. Islamic boarding schools are a gathering place for students from various cities in Indonesia. If there are no prevention efforts at the Islamic boarding school, there will be a new covid19 virus cluster. Community service activities through the partnership program for the Al Mujaddadiyah Islamic Boarding School are focused on developing technology to overcome the prevention of the Covid19 virus in the Islamic boarding school environment. The hope is that with this training, boarding school caregivers and students can better understand the health protocols applied to technology to prevent the spread of the Covid19 virus in the cottage environment.